Strain collection of Rhizobium spp. isolated from arboreus legumes in the state of Ceará, Brazil - Vasconcelos, Ilo; Almeida, Rogério Tavares de; Landim, Célia M.U. (Pesquisa Agropecuaria Brasileira, 2014)
This collection is a listing of 190 Rhizobium spp. strains available for distribution to research workers and inoculum producers by the Soil Microbiology Laboratory of the Soil Science Department of the Universidade Federal do Ceará, Brazil. Most of the plants from which the strains were collected are native or cultivated in Northeast Brazil. The local strains were tested for purity by the streak plate method and trials for nodulation under laboratory conditions were provided. Several strains came from other Brazilian and foreign laboratories. All the cultures are preserved in YMA with bromthymol blue, under mineral oil.